Limiting process for integral functionals of a wiener process on a cylinder - Koval, Yu. B. (Ukrains’kyi Matematychnyi Zhurnal, 1994)
We prove that integral functionals, whose integrands are bounded functions of a Wiener process on a cylinder, weakly converge to the process$w_1(τ(t)),\, τ(t) = β_1 t + (β_2 − β_1) \text{mes} \{s:w 2(s) ≥ 0,\, s < t\}$, where $w_1(t)$ and $w_2(t)$ are independent one-dimensional Wiener processes, $β_1$ and $β_2$ are nonrandom values, and $β_2 ≥ β_1 ≥ 0$.